2002
DOI: 10.1590/s0066-782x2002001300007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hemodynamic effects of saline infusion to maintain volemia on temporary abdominal aortic occlusion

Abstract: Objective -To analyze hemodynamic and metabolic effects of saline solution infusion in the maintenance of blood volume in ischemia-reperfusion syndrome during temporary abdominal aortic occlusion in dogs.Methods -We studied 20 dogs divided into 2 groups: the ischemia-reperfusion group (IRG, n=10) and the ischemia-reperfusion group with saline solution infusion aiming at maintaining mean pulmonary arterial wedge pressure between 10 and 20 mmHg n=10 . Severe hypotension, associated with a decrease in cardiac o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As demonstrated in several studies, saline infusion with maintenance of mean pulmonary arterial wedge pressure is suitable for minimizing hemodynamic changes after release of the aortic clamps, mainly avoiding hypotension and a decrease in cardiac index (5)(6)(7)(13)(14)(15). However, in the present study this procedure caused worsening of gas exchange as shown by an increase in P(A-a)O 2 after aortic declamping in IRG-SS, determining a progressive decrease in PaO 2 .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…As demonstrated in several studies, saline infusion with maintenance of mean pulmonary arterial wedge pressure is suitable for minimizing hemodynamic changes after release of the aortic clamps, mainly avoiding hypotension and a decrease in cardiac index (5)(6)(7)(13)(14)(15). However, in the present study this procedure caused worsening of gas exchange as shown by an increase in P(A-a)O 2 after aortic declamping in IRG-SS, determining a progressive decrease in PaO 2 .…”
Section: Discussionmentioning
confidence: 50%
“…Maintenance of pulmonary artery wedge pressure between 10 and 18 mmHg during this procedure could prevent a decline in cardiac output and hypotension after aortic declamping (5)(6)(7)(13)(14)(15). However, few studies have evaluated the impact of fluid infusion on pulmonary gas exchange.…”
Section: Introductionmentioning
confidence: 99%